2006
DOI: 10.1016/j.jpainsymman.2005.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Brief Coping Skills Training Intervention on Nociceptive Flexion Reflex Threshold in Patients Having Osteoarthritic Knee Pain: A Preliminary Laboratory Study of Sex Differences

Abstract: Studies have documented the efficacy of coping skills training (CST) for managing pain, distress, and disability in persons with arthritis. However, no laboratory studies have examined the effects of CST on descending modulation of nociception. This study used the nociceptive flexion reflex (NFR) to document pain and nociceptive responding among 62 men and women with osteoarthritis of the knee (mean age=63.3+/-7.5 years). Before and after a 45-minute CST session, participants completed laboratory assessments o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…This may be associated with the higher reported pain intensity scores for women than for men, but may also be due to the greater impact on function, as assessed by the WOMAC, in women than in men (mean ± SD WOMAC score 51.6 ± 17.2 versus 44.4 ± 18.1; P < 0.0001). Several other studies have already demonstrated differences in the coping strategies developed by men and women in the face of persistent pain (25–29). Women are more likely than men to use emotion‐focused coping strategies when dealing with OA pain (25), and this is particularly true for pain catastrophizing (27).…”
Section: Discussionmentioning
confidence: 99%
“…This may be associated with the higher reported pain intensity scores for women than for men, but may also be due to the greater impact on function, as assessed by the WOMAC, in women than in men (mean ± SD WOMAC score 51.6 ± 17.2 versus 44.4 ± 18.1; P < 0.0001). Several other studies have already demonstrated differences in the coping strategies developed by men and women in the face of persistent pain (25–29). Women are more likely than men to use emotion‐focused coping strategies when dealing with OA pain (25), and this is particularly true for pain catastrophizing (27).…”
Section: Discussionmentioning
confidence: 99%
“…For example, mental imagery involves distraction from pain and positive emotions, both of which activate cortical and brainstem structures at the origin of descending pain inhibition (Bantick et al, 2002;Tracey et al, 2002;Valet et al, 2004) and reduce human spinal nociception (Willer et al, 1979;Rhudy et al, 2005;Ruscheweyh et al, 2011). Similarly, relaxation techniques reduce human spinal nociception (Emery et al, 2006). In addition, a parallel reduction of RIII size and pain perception is usually considered a strong indication of the activation of descending pain modulatory systems (Willer et al, 1979;Rhudy et al, 2005;Sandrini et al, 2005;Ruscheweyh et al, 2011).…”
Section: Interpretation Of Learned Riii Reductionmentioning
confidence: 99%
“…It is interesting to note that meditation/mindfulness stress management programs, unlike CBT ones, do not address coping skills in their protocol. However, different clinical trials showed long-term efficacy of coping skill training for better emotional control [85], quality of life [86,87], and resiliency enhancement [88]. …”
Section: Discussionmentioning
confidence: 99%